Treatment Strategy: Role of Enfuvirtide in Managing Treatment-Limiting Side Effects. (2007) - Tsoukas, Christos
Abstract : Side effects can limit the options available to physicians for the treatment of HIV infection. Management of these side effects is essential, to avoid cessation of treatment. The entry inhibitor enfuvirtide can be useful as one of three active agents in an HIV treatment regimen as a way to both reduce treatment-limiting side effects and provide an efficacious agent for viral control. In the present case, the patient had a problematic and lengthy treatment history, with numerous concomitant conditions. His latest regimen, which includes an agent in a new drug class (enfuvirtide), has maintained HIV suppression while minimizing toxicity.